Rapid Analysis of Polar Components in Ophiocordyceps sinensis by Conventional Liquid Chromatography System - Li, Wen-qing; Li, Wen-jia; Qian, Zheng-ming; Chen, Shi-lin; Xiang, Li (Chinese herbal medicines, 2014)
Objective To develop a rapid high-performance liquid chromatography coupled with diode array detection （HPLC-DAD） method for the simultaneous determination of six polar compounds in Ophiocordyceps sinensis. Methods A poroshell SB Aq column （50 mm × 4.6 mm, 2.7 μm） and gradient elution were used; The detection wavelength of compounds was set at 260 nm. The chromatographic peaks of the six investigated compounds in sample were identified by comparing their retention times with reference compounds. Results All calibration curves showed good linearity （r〉 0.999） within the tested ranges. The intra- and inter-day precisions of the six analytes were less than 0.8% and 2.1%, respectively, and the recoveries of the six analytes were between 95% and 103%. The validated method was successfully applied to the determination of six polar compounds in O. sinensis samples. Conclusion The poroshell SB Aq column is suitable for the rapid analysis of polar components in Chinese materia medica on conventional HPLC system and the developed HPLC method is also helpful to the quality control of O. sinensis.